1959
DOI: 10.2337/diab.8.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Uptake and Response to Insulin of the Isolated Rat Diaphragm: The Effect of Denervation

Abstract: It has been known for many years that exercise decreases the insulin requirements of diabetics and increases glucose uptake from the blood even in untreated diabetic subjects. 1 Ingle 2 ' 3 demonstrated that severe work can cause a drop in blood sugar to extremely low levels in partially depancreatized diabetic rats receiving no insulin and that the effects of insulin and work are additive. Levine and his co-workers* investigated the effect of muscular work on the volume of distribution of nonmetabolizable mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
3

Year Published

1981
1981
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 1 publication
1
28
1
3
Order By: Relevance
“…Among the possible mechanisms, insulin could conceivably stimulate NO release by a direct, local effect at the vascular endothelium, as previously suggested (13), or indirectly through the activation of a cholinergically mediated stimulation of NO release, as proposed in liver (14). Evidence for cholinergic neurogenic vasodilation in skeletal muscle has been provided in many animal species (15)(16)(17)(18), and interruption of nerve supply to skeletal muscle was shown to result in the development of insulin resistance in the affected muscle (19). Furthermore, applying atropine during the infusion of insulin in anesthetized cats and rats was reported to reduce the effect of insulin on glucose uptake in skeletal muscle (14,20).…”
mentioning
confidence: 78%
“…Among the possible mechanisms, insulin could conceivably stimulate NO release by a direct, local effect at the vascular endothelium, as previously suggested (13), or indirectly through the activation of a cholinergically mediated stimulation of NO release, as proposed in liver (14). Evidence for cholinergic neurogenic vasodilation in skeletal muscle has been provided in many animal species (15)(16)(17)(18), and interruption of nerve supply to skeletal muscle was shown to result in the development of insulin resistance in the affected muscle (19). Furthermore, applying atropine during the infusion of insulin in anesthetized cats and rats was reported to reduce the effect of insulin on glucose uptake in skeletal muscle (14,20).…”
mentioning
confidence: 78%
“…Denervation of skeletal muscle has been shown to cause insulin resistance. 14 Schmalbruch et al 15 studied the morphology of rat soleus muscle denervated for 6 ± 10 months. These investigators found that in chronically denervated muscle, the original ®bers were lost and those surviving were adversely a ected by repeated cycles of regeneration and necrosis.…”
Section: Determinants Of Insulin Resistancementioning
confidence: 99%
“…These interpretations are based on insulin values from 1 fasting time point and may indicate a different outcome had they been based on a 2-hour postprandial glucose load; however, HOMA-IR has been indicated as a valid measure of impaired glucose tolerance in lieu of a glucose challenge (8,89). Insulin resistance in spinal cord dysfunction appears to be directly related to denervation of skeletal muscle (90). There were no SB or SCI subjects with glucose intolerance; however, 8.8% of SB, 30.0% of SCI, and 16.7% of controls had hyperinsulinemia and/or insulin resistance based on fasting insulin concentrations and/or HOMA-IR values, even though known diabetes was an exclusion criterion.…”
Section: Discussionmentioning
confidence: 99%